Pengaruh pemberian daun salam terhadap peningkatan kadar hemoglobin pada ibu hamil trimester III di PMB Luky Handayani Dusun Gumuksari Desa Nogosari - Handayani , Luky; Wijayanti, Tut Rayani Aksohini (PT WIM Solusi Prima, 2025)
During pregnancy, the body has more iron due to increased blood and oxygen. Its deficiency can cause risks during childbirth. The signs are such as tiredness, dizziness, paleness and shortness of breath. With treatment supplements, nutritious food and routine checks. In 2019, reaching 48.9% the prevalence of anemia in Indonesia experienced a significant increase compared to the 2013 Riskesdas data which was recorded at 37.1% in pregnant women. The purpose of this study was to understand the administration of bay leaves to increase hemoglobin levels in PMB Luky Handayani, Gumuksari Hamlet, Nogosari Village in pregnant women in the third trimester. This study was conducted in a quasi-experimental design utilizing the Pretest-Posttest with control group design approach. 32 respondents in the third trimester were divided into two groups, namely the intervention group (bay leaves + Fe pills) and the non-intervention group (Fe tablets only) in pregnant women. Normality testing used the Shapiro Wilk Test, data analysis used the Wilcoxon Signed Ranks test to see the effect in each group and the Mann Whitney test on comparisons between groups. The Wilcoxon test showed results (p<0.05) of significant increase in Hb levels between the two groups. The Mann Whitney test indicated a significant difference between the intervention and non-intervention groups with a value of (p=0.032) which means that giving bay leaves together with Fe tablets is more efficient in increasing Hb levels compared to only giving Fe tablets. Conclusion. Decoction of bay leaves given with Fe tablets is efficient in increasing hemoglobin levels in the third trimester and can be used as a supportive therapy to overcome anemia in pregnant women. Saat hamil, tubuh lebih banyak zat besi karena peningkatan darah dan oksigen. Kekurangannya bisa sebabkan resiko saat melahirkan. Tanda-tandanya seperti lelah, pusing, pucat dan sesak. Dengan pengobatannya suplemen, makan bergizi dan kontrol rutin. Pada tahun 2019, mencapai 48,9% prevalensi anemia di Indonesia mengalami kenaikan signifikan dibandingkan data tahun 2013 Riskesdas yang tercatat senilai 37,1% dalam ibu hamil. Tujuan penelitian ini yaitu memahami pemberian daun salam pada trimester III kenaikan kadar hemoglobin di PMB Luky Handayani Dusun Gumuksari Desa Nogosari pada ibu hamil. Studi ini dilaksanakan dalam desain kuasi eksperimental memanfaatkan pendekatan Pretest-Posttest With Control Group Design. 32 responden trimester III pembagiannya terdiri dua kelompok yakni kelompok intervensi (daun salam + Pil Fe) dan kelompok non-intervensi (tablet Fe saja) pada ibu hamil. Pengujuan normalitasnya menggunakan Shapiro Wilk Test, data analisis menggunakan uji Wilcoxon Signed Ranks untuk melihat pengaruh dalam masing-masih kelompok dan Mann Whitney test pada perbandingan diantara kelompok. Uji Wilcoxon menunjukkan hasil (p<0,05) peningkatan kadar Hb signifikan antar dua kelompok. Uji Mann Whitney mengindikasikan perbedaan signifikan kelompok intervensi serta non-intervensi senilai (p=0,032) yang berarti pemberian daun salam bersama tablet Fe lebih efisien dalam menaikkan kadar Hb dibandingkan hanya diberi tablet Fe saja. Kesimpulan. Rebusan daun salam yang diberikan bersama tablet Fe efisien untuk menaikkan kadar hemoglobin trimester III dan dapat dijadikan sebagai terapi pendukung untuk mengatasi anemia pada ibu hamil.